Aberration measurement of the probe-forming system of an electron microscope using two-dimensional materials - Sawada, H; Allen, C; Wang, S; Warner, J; Kirkland, A (Elsevier, 2017)
The geometric and chromatic aberration coefficients of the probe-forming system in an aberration corrected transmission electron microscope have been measured using a Ronchigram recorded from monolayer graphene. The geometric deformations within individual local angular sub-regions of the Ronchigram were analysed using an auto-correlation function and the aberration coefficients for the probe forming lens were calculated. This approach only requires the acquisition of a single Ronchigram allowing rapid measurement of the aberration coefficients. Moreover, the measurement precision for defocus and two-fold astigmatism is improved over that which can be achieved from analysis of Ronchigrams recorded from amorphous films. This technique can also be applied to aberration corrected STEM imaging of any hexagonal two-dimensional material.